Content Validity, Face Validity and Reliability for Malay Version of The Stages Of Change Readiness and Treatment Eagerness Scale for Smoking Cessation (M-SOCRATES-S) and Malay Version of Smoking Self-Efficacy (M-SSE) - Mohamed, Mohd Haazik; Voo, Peter; Maakip, Ismail; Robinson, Fredie; George Albert, Wanda Kiyah (Asian Social Work Journal, 2024)
A set of questionnaires on smoking behaviour are required in order to conduct a full assessment of smoking issues in Malaysia. Therefore, this study was conducted to ensure that the Malay Version of The Stages of Change Readiness and Treatment Eagerness Scale for Smoking Cessation (M-SOCRTAES-S) and Malay Version of Smoking Self-Efficacy (M-SSE) questionnaires can be used systematically in Malaysia. The permission to adapt these two questionnaires for the publishers was made and permission was obtained. This questionnaire has been translated into Malay using the direct translation method. Two experts were involved in the content validity process while eight lay adult smokers were involved in the face validity process while a total of 50 adult smokers were involved in the reliability assessment process. The results of the study found that the S-CVI/Ave and S-CVI/UA values ​​for M-SOCRATES-S are 0.97 and 0.94 while the S-CVI/Ave values ​​and S-CVI/UA values ​​for M-SSE are 1.0 and 1.0. The S-FVI/Ave and S-FVI/UA values ​​for M-SOCRATES-S are 0.99 and 0.95 while the S-FVI/Ave and S-FVI/UA values ​​for M-SSE are 0.98 and 0.83. There are three domains in the M-SOCRATES-S questionnaire, namely the recognition domain, the ambivalent domain and the taking action domain, these three domains recorded Cronbach's alpha values ​​of 0.85, 0.80 and 0.89. While there are two domains in the M-SSE, namely internal and external, which recorded Cronbach's alpha values ​​of 0.81 and 0.77. The findings of this study show that the content validity, face validity, and reliability of these two questionnaires are acceptable and that they may be utilised among Malaysian adult smokers who can speak and write Malay.